The Management System: Its Functions and Processes - Cunningham, J. Barton (Management Science, 1979)
What is management? In recent years, a number of schools or approaches to management have evolved. What is rather upsetting to the manager is that there are a variety of unrelated approaches without any suggestion of their relationship to each other. Even more upsetting is that some of these approaches seem to be based on the disciplines of particular researchers rather than their ability to help managers. The study explores the rationale underlying two predominant orientations. One is concerned with the process of management, while the other emphasizes the function of management. The managerial process involves such intuitive principles as planning, organizing, and staffing. The managerial function involves arranging equipment to perform functions such as procurement, production, and adaptation. The goal is to illustrate the relationship of these approaches to each other and to specific managerial needs. The study was conducted among top managers in six municipal organizations. The research utilized a questionnaire and decision-making simulation for gathering data on the relationship of each managerial orientation. The results indicate that each orientation deals with different areas of managerial action. Key managerial processes focus on integrating, making decisions, recording information, motivating, and negotiating. The managerial functions, in this study, are part of three subsystem efforts which are administrative, adaptive, and technical. When management is defined as a process, it has no relationship to functions; when it is defined as functions of specific subsystems, there is no positive relationship to the process.